In-medium effects in strangeness production in heavy-ion collisions at (sub-) threshold energies - Song Taesoo; Tolos Laura; Wirth Joana; Aichelin Joerg; Bratkovskaya Elena (EPJ Web of Conferences, 2022)
We study the in-medium effects in strangeness production in heavyion collisions at (sub-)threshold energies based on the microscopic Parton-Hadron-String Dynamics (PHSD) transport approach. The in-medium modifications of the antikaon properties are described via the self-consistent coupledchannel unitarized scheme based on a SU(3) chiral Lagrangian while the inmedium modification of kaons are accounted via the kaon-nuclear potential, which is assumed to be proportional to the local baryon density. We find that the modifications of (anti)kaon properties in nuclear matter are necessary to explain the experimental data in heavy-ion collisions.